2010
DOI: 10.1038/gt.2010.36
|View full text |Cite
|
Sign up to set email alerts
|

Immune reactivity to type VII collagen: implications for gene therapy of recessive dystrophic epidermolysis bullosa

Abstract: Recessive dystrophic epidermolysis bullosa (RDEB) is a severe genodermatosis caused by loss-of-function mutations in COL7A1 encoding type VII collagen, the component of anchoring fibrils. As exogenous type VII collagen may elicit a deleterious immune response in RDEB patients during upcoming clinical trials of gene therapies or protein replacement therapies, we developed enzyme-linked immunosorbent assay (ELISA) and enzyme-linked immunosorbent spot (ELISPOT) assays to analyze B-and T-cell responses, to the ful… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
26
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 50 publications
2
26
0
Order By: Relevance
“…Several immunoassays have been developed so far for the detection of autoantibodies against collagen VII (Table 2) [22,25-27]. To further improve the detection of collagen VII-specific autoantibodies, in the present study we have generated a chimeric antigen substrate containing virtually all autoepitopes, which have been reported in previous epitope mapping studies in patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several immunoassays have been developed so far for the detection of autoantibodies against collagen VII (Table 2) [22,25-27]. To further improve the detection of collagen VII-specific autoantibodies, in the present study we have generated a chimeric antigen substrate containing virtually all autoepitopes, which have been reported in previous epitope mapping studies in patients.…”
Section: Discussionmentioning
confidence: 99%
“…For detection of collagen VII-specific IgG autoantibodies by ELISA, immunoassays using recombinant forms of the NC1 domain or the full-length molecule have been developed [22,25-27]. Based on B cell epitope in silico prediction and wetlab mapping studies, a recombinant form of collagen VII containing both the NC1 and NC2 domains as well as the hinge region would allow a most sensitive detection of anti-collagen VII antibodies in patients.…”
Section: Introductionmentioning
confidence: 99%
“…Direct IF and indirect IF on rat and/or monkey esophagus and salt-split skin, as well as antinuclear antibodies, were routinely processed, and direct immunoelectron microscopy and ELISA for type VII collagen were performed as previously described (Prost et al, 1987;Pendaries et al, 2010).…”
Section: Immunological Studiesmentioning
confidence: 99%
“…A previous smaller study found that 1 of 7 RDEB patients exhibited anti-C7 antibodies by ELISA (Pendaries et al, 2010). In accordance with our data herein, a recent study of 17 RDEB patients showed that 15 of 17 of the patients exhibited anti-C7 antibodies (Tampolini et al, 2013).…”
mentioning
confidence: 93%